Implementasi Model Learning Together untuk Meningkatkan Keterampilan Leadership pada Materi Keliling dan Luas Bangun Datar di Sekolah Dasar - Syifa Apriyanti; Nurhidayati Nurhidayati; Riskia Pangestika (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was carried out with the aim of improving students' leadership skills through the Learning Together model with material on the perimeter and area of flat figures for class IV. This research uses classroom action research carried out at SD Negeri 1 Pohkumbang. The subjects of this research were all 20 grade IV students at SD Negeri 1 Pohkumbang. The instruments used are observation, interviews, tests and documentation. Data analysis techniques are carried out using qualitative methods in the form of descriptive and quantitative methods of presenting data and drawing conclusions. The results of the research show that the skills in implementing the Learning Together model can improve students' leadership skills with the percentage results for cycle I 35% and cycle II 85% which are categorized as good.